The effectiveness of Vietnamese policies response to climate change through ARDL analysis - Le Hoang Nghiem (HO CHI MINH CITY OPEN UNIVERSITY JOURNAL OF SCIENCE, 2021)
Being a highly vulnerable country due to climate change, Vietnam has issued various climate policies while trying to keep the pace of economic growth. The study evaluates the effectiveness of these policies by examining the effect of economic and energy factors in the efforts of controlling CO2 emissions. Approach by Autoregressive Distributed Lag (ARDL) analysis, the model of a linear regression between CO2 emissions and Gross Domestic Product (GDP), Foreign Direct Investment (FDI) & sources of energy consumption has been developed from 1985 to 2018. The study indicates that the economic factor as Foreign Direct Investment (FDI) is a possible significant element to mitigate the emission. In addition, sources of energy consumption have the important role of controlling CO2 emissions. In the long run, the consumption of non - renewable energy is a positive and significant effect on CO2 emissions while renewable energy is vice versa. These outcomes show the Foreign Direct Investment (FDI) and renewable energy consumption factors lead to the decrease of CO2 emissions in the long run for Vietnam, which implies the co-exist of economic growth and decarbonization.